2016
DOI: 10.7554/elife.19531
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of herbivore-induced early defense signaling was shaped by genome-wide duplications in Nicotiana

Abstract: Herbivore-induced defenses are widespread, rapidly evolving and relevant for plant fitness. Such induced defenses are often mediated by early defense signaling (EDS) rapidly activated by the perception of herbivore associated elicitors (HAE) that includes transient accumulations of jasmonic acid (JA). Analyzing 60 HAE-induced leaf transcriptomes from closely-related Nicotiana species revealed a key gene co-expression network (M4 module) which is co-activated with the HAE-induced JA accumulations but is elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 111 publications
0
23
0
Order By: Relevance
“…These results suggested that JA production or signal transduction is physiologically constrained in the “signal non-responsive” species. To test this hypothesis, we investigated the transcriptomes of 4 of the species ( N. attenuata , N. miersii , N. pauciflora and N. obtusifolia ) induced by W+W, W+OS Ms and W+OS Sl ( 53 ). Consistent with the pattern of metabolome reconfigurations, species were well-separated in the transcriptomic space with N. attenuata exhibited the highest OS-induced RDPI while N. obtusifolia being the lowest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that JA production or signal transduction is physiologically constrained in the “signal non-responsive” species. To test this hypothesis, we investigated the transcriptomes of 4 of the species ( N. attenuata , N. miersii , N. pauciflora and N. obtusifolia ) induced by W+W, W+OS Ms and W+OS Sl ( 53 ). Consistent with the pattern of metabolome reconfigurations, species were well-separated in the transcriptomic space with N. attenuata exhibited the highest OS-induced RDPI while N. obtusifolia being the lowest (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Analyses on the herbivory-induced conserved transcriptomic responses in Nicotiana further showed that insertions of DTT-NIC1 are significantly enriched within the 1-kb upstream region of herbivory-induced early defense signaling genes in N. attenuata, and may have contributed to the recruitment of genes into the induced defense signaling network by introducing WRKY transcription factor binding sites (17).…”
Section: Resultsmentioning
confidence: 99%
“…The 44K 60-mer oligonucleotide microarrays designed for N. attenuata transcriptome analysis (Agilent) were used. cDNA preparation, hybridizations, and data analysis were performed as previously described (79). Probes were filtered by 1.5-fold change and adjusted P values are less than 0.05.…”
Section: Methodsmentioning
confidence: 99%